2022
DOI: 10.1249/jes.0000000000000281
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise Prescription for Osteoporosis: Back to Basics

Abstract: Optimum loading for bone was determined from animal studies in the 1980s, yet practical translation has only recently been applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 102 publications
(130 reference statements)
0
14
0
1
Order By: Relevance
“…The inclusion of women whose ages fell within a wide range and who were of varying menopausal status might also have diluted the effect of PA on bone microarchitecture, as individuals with the lowest bone mass may have the largest response to mechanical loading. [ 39,44 ] However, the analyses were adjusted for age, and the results were similar when adjusted for age or menopausal status. Finally, voluntary participants might be prone to healthy selection bias, which affects the generalizability of the results.…”
Section: Discussionmentioning
confidence: 92%
“…The inclusion of women whose ages fell within a wide range and who were of varying menopausal status might also have diluted the effect of PA on bone microarchitecture, as individuals with the lowest bone mass may have the largest response to mechanical loading. [ 39,44 ] However, the analyses were adjusted for age, and the results were similar when adjusted for age or menopausal status. Finally, voluntary participants might be prone to healthy selection bias, which affects the generalizability of the results.…”
Section: Discussionmentioning
confidence: 92%
“…4 Improved muscle strength exerts a greater force on bone than gravity; decreased muscle force is associated with bone loss. 21 A systematic review on the effects of different exercise regimens on bone health found that all exercise interventions were effective in preventing bone loss compared with no exercise program, while mind-body exercises were most effective at minimizing vertebral BMD loss. 22 The latter exercises are characterized by slow, gentle, and coordinated movements with breathing suitable for older adults.…”
Section: Physical Activitymentioning
confidence: 99%
“…Resistance exercises using elastic exercise bands, weights, and weight machines increase muscle strength 4. Improved muscle strength exerts a greater force on bone than gravity; decreased muscle force is associated with bone loss 21…”
Section: Lifestyle Managementmentioning
confidence: 99%
“…For osteoporotic patients wanting to increase bone density, high intensity resistance and impact training will be useful. 92 For the rest of us, reaching personal goals – whether they are cardiometabolic, endurance, or strength – is achievable with consistent application.…”
Section: Prescribing Exercise As Medicinementioning
confidence: 99%